The influence of Financial Technology on Impulse Buying in Gen Z moderated by Financial Literacy - Sulistyowati, Shanti Nugroho (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The aim of this research is to examine the influence of Financial Technology on impulse buying in Gen Z which is moderated by financial literacy. This study uses a quantitative approach. The sample used was 89 respondents from economic education study program students using fintech payment applications. Samples were taken using the purposive sampling method. Data analysis using the SmartPLS application. The results of the research show that financial technology related to the use of fintech payments has a negative influence on impulsive purchases but is not significant. Financial literacy has a negative influence on impulsive purchases but is not significant. Financial literacy significantly weakens the influence of fintech on impulsive purchases. The research results cannot be generalized to Gen Z on research objects in different places.